ELLIPTIC CURVE CRYPTOGRAPHY - Meleshko, O. O.; Kovalskiy, O. O. (Science-based technologies, 2014)
In this article main points of ECC’s application and structure is reviewed.Here is described the main advantages of ECC. The aim of this article is to systematize information on the practical application of elliptic curves,its general terms ,affect the topic of ECC popularity.Another interesting part of article is the question of patents,in most of Certicoms patents. Assuring fact is that the question of ECC is discovered by ECC Workshop, since 1997 were hold a series of conferences on the ECC theme.The last one takes place in 2013 year. Since the first ECC workshop, held 1997 in Waterloo, the ECC conference series has broadened its scope beyond elliptic curve cryptography and now covers a wide range of areas within modern cryptography.The table in the end of article compares key sizes,and main points of ECC and RSA.The conclusion is that ECC provides much more confidence use than first-generation public key cryptography systems. Equations based on elliptic curves is easy to perform, and extremely difficult to reverse and it is in demand.